The influence of family relations on decision making in family businesses - Aleksandra Stoilkovska; Violeta Milenkovska; Gordana Serafimovic (UTMS Journal of Economics, 2013)
The peculiarity and uniqueness of family businesses set them apart from other businesses in many things. Natural need of man to survive in these harsh circumstances forces him to constantly seek new sources of funding or simply tries to improve the existing. Secure existence is difficult to ensure. The successful family business provides many benefits: reliable operation, to be your own boss, flexible working hours, family members are taken care of, to become successful with your own strengths. Also this kind of business brings a range of difficulties that have to be overcomed. Apart from the daily struggle for enterprise development in the complex conditions of tough competition and rapid changes in the environment, family businesses face problems of internal character. Namely, the parents are thorn between the family relations, the love towards their children and the consistence in the decision making processes. Although this is a modern and very present theme however owners of family businesses rarely dare to speak publicly on the subject. This paper presents an action research conducted on a sample of 26 family businesses in FYROM. This research study is primarily exploratory in nature, and the research instruments include survey through questionnaires with family member and employees that are not family members.
Keywords: M12; 330; family businesses; family relations; decision making; family members; non-family members